A novel method to uniquely determine the parameters in Gurson–Tvergaard–Needleman model. Issue 12 (22nd August 2021) - Zhang, Tairui; Lu, Kai; Mano, Akihiro; Yamaguchi, Yoshihito; Katsuyama, Jinya; Li, Yinsheng
Abstract: The Gurson–Tvergaard–Needleman (GTN) model is promising in failure prediction as it takes the micromechanical behavior of ductile metals into consideration. However, its engineering applications have scarcely progressed due to the difficulty in determining its eight strongly coupled parameters. Taking the physical background of GTN model into consideration, a set of methods was established to determine all parameters in the GTN model. The knowledge of continuum damage mechanics was introduced to experimentally determine the development of void volume fraction through an interrupted uniaxial tensile test, by which the three parameters regarding void nucleation were analytically derived. Other parameters in the GTN model were also uniquely determined through a joint use of the chemical composition analysis, the cell model analyses, and the inverse finite element method. Reliability of this novel parameter determination method was verified through failure predictions on both cracked and un‐cracked specimens of STPT410.